The influence of negative interest rates on life insurance companies - Nicolaus Grochola (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2023)
Between 2016 and 2022, life insurers in several European countries experienced negative longterm interest rates, which put pressure on their business models. The aim of this paper is to empirically investigate the impact of negative interest rates on the stock performance of life insurers. To measure the sensitivities, I estimate the level, slope, and curvature of the yield curve using the Nelson-Siegel model and empirical proxies. Panel regressions show that the effect of changes in the level is up to three times greater in a negative interest rate environment than in a positive one. Thus, a 1ppt decline in long-term interest rates reduces the stock returns of European life insurers by up to 10ppt when interest rates are below 0%. I also show that the relationship between the level and the sensitivity to interest rates is convex, and that life insurers benefit from rising interest rates across all maturity types.
Keywords: G01; G18; G22; 330; Life insurance; interest rate risk; negative interest rates